Brain biomarkers in tench (Tinca tinca L.) after semi-static exposure to the pesticide carbofuran - Hernández-Moreno, David; Gil-Molinos, María; Bertini, Simone; Prado Míguez, María; Soler-Rodríguez, Francisco; Pérez-López, Marcos (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: The aquatic environment is continuously being contaminated with toxic chemical substances from industrial, agricultural and domestic activities. The identification of different biomarkers of such contamination is of great relevance to determine the potential impact of those xenobiotics on the health of organisms. Objective: To estimate the suitability of different biochemical brain biomarkers from tench in order to evaluate the environmental effect of an exposition to different concentrations of the pesticide carbofuran. Methods: The present study focused on the effect of a long-term exposure (28 days) to different concentrations (50, 100 and 200 μg/L) of the pesticide carbofuran on certain biochemical parameters of tench (Tinca tinca L.). Selected biomarkers for stress monitoring were malondialdehyde (MDA), as index of lipid peroxidation, and reduced glutathione (GSH). Moreover, acetylcholinesterase (AChE) activity was quantified as biomarker of effect on fish nervous system. Results: AChE activity was significantly inhibited in fish exposed to all concentrations of carbofuran after 14 and 21 days of exposure, returning to basal levels after this period with 50 and 100 μg/L. Moreover, significant decreases of MDA levels could be detected after 14 and 21 days of exposure to 200 μg/L, lasting until the end of the experiment. GSH levels decreased after 14 and 21 days of exposure to 100 and 200 μg/L; nevertheless, GSH recovered basal levels at the end of the experiment. Conclusion: All the three biochemical parameters assessed -mainly inhibition of AChE activity- could be adequate biomarkers of early exposition (less than 14 days) to low doses of carbofuran in biomonitoring programs, being MDA reduction also related to longer exposure.